VOA English Learning YouTube Channel as a Speaking Skill Learning Media : Case Study of Students’ Perception at University HKBP Nommensen Pematangsiantar (UHKBPNP) - Irene Adryani Nababan; Berlin Sibarani; Anita Sitanggang (International Journal of Educational Research Excellence (IJERE), 2024)
This research aims to investigate the perceptions of first-semester students in the English Education Department at the University of HKBP Nommensen Pematangsiantar (UHKBPNP) regarding the use of the VOA English Learning YouTube channel as a tool for improving speaking skills, as well as to identify the benefits that students gain from its use. A qualitative descriptive approach was adopted for this study, with questionnaires serving as the primary instrument for data collection. The study population consisted of 38 first-semester students from the PIA1 class in the English Education Department at UHKBPNP. The findings indicated that students held a favorable view of the VOA English Learning YouTube channel as a medium for learning speaking skills. The respondents' positive feedback was based on their personal learning experiences with the channel. They reported that the channel had a beneficial impact on their speaking practice after engaging with the content from the VOA English Learning YouTube channel. Students found the channel both interesting and effective for learning speaking skills. Additionally, the research highlighted several benefits, including an increase in vocabulary and a reduction in the fear of pronouncing words.